Prevalência e fatores associados ao excesso de peso em São Francisco do Conde, Bahia - Oliveira, Luciana Carneiro de (2014)
Overweight is characterized by the accumulation of body above the recommended values and acceptable fat, and today has ceased to be considered an individual problem and last to be treated as a major public health problem affecting both developed and developing countries Although there are reliable and current population information on the characterization of the anthropometric status in adults , referring to regions of the country , few cities have such information from population-based studies . Objective: To describe the prevalence of overweight in adults enrolled in the Family Health Program (FHP) in São Francisco do Conde, Bahia, according to sociodemographic, and lifestyle variables . Methods: Epidemiological study of secondary cross-section of a Research and Extension Proposal for Health Surveillance for the detection of minor psychiatric disorders and hypertension in São Francisco do Conde, Bahia, 2010. Research conducted with a random sample of individuals aged over 18 years, registered at the Family Health Program. Data were collected through home visits by students of Medicine, State University of Feira de Santana, which form applied previously tested and have carried out measurement of physical parameters (weight, height and waist circunferencia) of the participants . Data were processed and analyzed using the Epi Data 3.1 and SPSS 9.0 (SSAEE / DAS / UEFS). Results: The prevalence of overweight was 58.1 % . Higher in females, among married individuals , among those who reported having more than three children , among those who reported being ex - smokers and self-reported hypertension . Conclusion: The results of this study showed high prevalence of overweight in São Francisco do Conde in adults of both sexes , especially in females which justifies the adoption of specific actions aimed at reducing this problem.